Chemical Composition, Antioxidant and Antibacterial Efficacy of Alkanna syriac Bioss. - Mohammad Sadaka , Mohammad Waleed (Latakia University Journal -Basic Sciences Series, 2019)
Chemical composition Chemical composition of hexanic extract of roots of Syrian Alkanna syriac Bioss. was determined by GC/MS. The extract contain 49 components, accounting for 99.33 % of total content. The major components determined were Arnebin 10.94%, Benzoic acid, 2,3,4,5,6-pentamethoxy-kaur-16-ene 9.36%, 1,8-dihydroxy-3-methyl-9,10-anthracenedione 4.62%, Trans-3'-methyl-4-(methylthio) chalcone 6.62%. The antioxidants activities of EtOAc extract of Alkanna syriac were studied, and IC50 was 474.4 ppm. The three extract (Hexanic, ethyl acetate, and ethanolic) showed completely inhabitation at 2 mg/ml for Staphylococcus aureus and S. albus, but there are no activities against Streptococcus pneumonia and Escherichia coli.